2004
DOI: 10.1037/0096-3445.133.4.573
|View full text |Cite
|
Sign up to set email alerts
|

Learning Nonadjacent Dependencies: No Need for Algebraic-Like Computations.

Abstract: Is it possible to learn the relation between 2 nonadjacent events? M. Peña, L. L. Bonatti, M. Nespor, and J. Mehler (2002) claimed this to be possible, but only in conditions suggesting the involvement of algebraic-like computations. The present article reports simulation studies and experimental data showing that the observations on which Peña et al. grounded their reasoning were flawed by deep methodological inadequacies. When the invalid data are set aside, the available evidence fits exactly with the predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(118 citation statements)
references
References 46 publications
(100 reference statements)
2
115
1
Order By: Relevance
“…For instance, Pen˜a, Nespor, Bonatti, and Mehler (2002) presented what they construed as a demonstration that detection of nonadjacent dependencies, which is a prerequisite to dealing with a PSG grammar, needs rulebased language-specific mechanisms, and Fitch and Hauser (2004) claimed to have provided evidence that the mastery of a PSG distinguishes human from nonhuman primates. However, these conclusions were weakened by major theoretical and methodological drawbacks (see Perruchet, Tyler, Galland, & Peereman, 2004, for a reappraisal of Pen˜a et al, and Perruchet & Rey, in press, for a reappraisal of Fitch & Hauser). By and large, the early claims of Chomsky are no longer the focal point of recent debates.…”
Section: The Innatist Chomskyan Perspectivementioning
confidence: 94%
“…For instance, Pen˜a, Nespor, Bonatti, and Mehler (2002) presented what they construed as a demonstration that detection of nonadjacent dependencies, which is a prerequisite to dealing with a PSG grammar, needs rulebased language-specific mechanisms, and Fitch and Hauser (2004) claimed to have provided evidence that the mastery of a PSG distinguishes human from nonhuman primates. However, these conclusions were weakened by major theoretical and methodological drawbacks (see Perruchet, Tyler, Galland, & Peereman, 2004, for a reappraisal of Pen˜a et al, and Perruchet & Rey, in press, for a reappraisal of Fitch & Hauser). By and large, the early claims of Chomsky are no longer the focal point of recent debates.…”
Section: The Innatist Chomskyan Perspectivementioning
confidence: 94%
“…Earlier experimental studies (e.g., Cleeremans, 1993;Santelmann & Jusczyk, 1998) showed that learning nonadjacent dependencies, which is a prerequisite for detecting a center-embedded structure, is possible only when the distance between the to-be-associated elements does not exceed a very small number of elements. Other studies (Gomez, 2002;Newport & Aslin, 2004;Onnis, Monaghan, Richmond, & Chater, in press;Perruchet, Tyler, Galland, & Peereman, 2004) suggest that learning nonadjacent dependencies occurs only in conditions in which there is some extraneous reason to associate the relevant elements (e.g., when the prosodic pattern makes the relations salient).…”
Section: Discussionmentioning
confidence: 99%
“…Several proponents of "general associationist mechanisms" (e.g., Perruchet et al, 2004;Seidenberg et al, 2002) have suggested that such mechanisms may account for Peña et al's (2002) and Endress and Bonatti's (2007) results. However, these proposals only stated that the mechanisms of the generalizations may be associationist but not what they actually may be.…”
Section: Four Puzzles Solvedmentioning
confidence: 99%
“…However, the mechanisms of the generalizations remained elusive despite substantial research (e.g., Balaguer, Toro, Rodriguez-Fornells, & Bachoud-Lévi, 2007;Mueller, Bahlmann, & Friederici, 2008;Pacton & Perruchet, 2008;Perruchet, Tyler, Galland, & Peereman, 2004;Seidenberg, MacDonald, & Saffran, 2002). A particularly important issue concerns the question of whether these results can be explained by a single, associationist mechanism, or whether one needs to posit different kinds of mechanisms for the generalizations and the statistical computations, respectively.…”
mentioning
confidence: 99%